PENGARUH KEMANFAAATAN NPWP, PEMAHAMAN WAJIB PAJAK, KUALITAS PELAYANAN, SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK (Studi Empiris pada WP OP di Kabupaten Tegal) - Siti Masruroh; Zulaikha Zulaikha (Diponegoro Journal of Accounting, 2013)
The level of tax compliance in Tegal Regency is still low, especially individual taxpayers who do business. It can be seen from comparison between the number of registered taxpayers with the number of taxpayers who report tax return. This research aimed to analyze the effect of the benefits of TIN, taxpayer understanding, quality of services, and tax penalties on tax compliance. Primary data collection method used is a survey method using questionnaires media. Sampling was done by convenience sampling method. The number of questionnaires that can be analyzed is 70 questionnaires. Data analysis techniques used in this research is logistic regression analysis.  The results of this research showed that taxpayer understanding had positive and significant effect on tax compliance. Benefits of TIN, quality of services and tax penalties had no significant effect on tax compliance.